Variation in a range of mTOR-related genes associates with intracranial volume and intellectual disability - M. R. F. Reijnders (Nature Portfolio, 2017)
The mTOR pathway is a key regulator of normal brain development. Here, the authors identify de novo mutations in RHEB, an mTOR activator protein, in patients with intellectual disability associated with megalencephaly and find a role for RHEB in regulating neuronal soma size and migration in vitro and in vivo.